The mobile augmented reality application for improving learning of electronic component module in TVET - Muthu, Nalienaa; Abdul Aziz, Faieza; Abdullah, Lili Nurliyana; Omar, Muhd Khaizer; Mustaqim Nazar, Muhammad Amir (Universiti Malaysia Pahang Publishing, 2023)
Teens and young adults may get training in anything from the basics to advanced skills in various workplace and academic settings at Technical and Vocational Education Training and Education (TVET) institutions. Some aspects of teaching and learning in TVET cannot be articulated clearly, and trainees cannot perceive how things fit together. The study was conducted to determine the optimal platform to develop mobile Augmented Reality applications for TVET trainees and, to assess the TVET trainee’s readiness for AR-based mobile application training deployment. An online questionnaire was sent to trainees at Industrial Training Institute in Malaysia via the online system. A marker-based Augmented Reality application was created for the Basic Electronic Components module utilizing Unity software, the Vuforia engine, and C# script. Finally, the trainees were allowed to test the generated application. The trainees were interviewed to obtain data on their responses. The results indicate that 83% of the TVET trainees own and use android as the application platform. The results of the pre-test and post-tests used to gauge the success of the Augmented Reality application show that its usage in the sub-learning module significantly improved memory recalls for the TVET trainees. The outcomes showed that the Augmented Reality application suited the participants' learning needs and improved the effectiveness of their learning. The result from this project will serve as a pre-test for determining the most suitable platform to deploy the Augmented Reality application to be developed in the future.